Produksi Biogas dari Campuran Feses Sapi dan Ampas Tebu (Bagasse) dengan Rasio C/N yang Berbeda (Biogas Production from Mixture of Dairy Manure and Bagasse with Different C/N Ratio) - Trisno Saputra; Suharjono Triatmojo; Ambar Pertiwiningrum (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
he experiment was conducted to determine biogas quality produced from mixture of dairy manure and bagasse with different C/N ratio level, and to know the optimal mixture ratio. There were three group treatments based on C/Nratio level : C/N ratio 22, 30, and 35 with three replications each. Nine units of 20 litre batch-feeding digesters were used during 30 days examination. The main data were BOD, COD, pH and VFA values, total biogas volume, andmethane value. C/N ratio of dairy manure and bagasse was 22, 12, and 198. Dry matter mixture was 7%. BOD value was decreased 54.33%, 27.89%, and 42.86%, COD value was decreased 35.85%, 8.29%, and 27.88% and biogas wasproduced as much as 29.42 litre, 68.51 litre, and 114.73 litre by each treatment with methane values of 24.16%, 27.5%, and 23.38%. VFA value were 27.19 ml mol, 27.86 ml mol, and 30.73 ml mol respectively during operation. BOD andCOD value decrease, pH value, biogas temperature, and total biogas volume was different among treatment. The optimal mixture was C/N ratio 30 treatment. The results indicated that bagasse could be used as material mixture in biogas production.(Key words : Biogas, Dairy manure, Bagasse, C/N ratio, Methane)